2018
DOI: 10.1093/annweh/wxy022
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Fragments and Fungal Aerosol Composition in Sawmills

Abstract: Assessment of exposure to fungi has commonly been limited to fungal spore measurements that have shown associations between fungi and development or exacerbation of different airway diseases. Because large numbers of submicronic fragments can be aerosolized from fungal cultures under laboratory conditions, it has been suggested that fungal exposure is more complex and higher than that commonly revealed by spore measurements. However, the assessment of fungal fragments in complex environmental matrix remain lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 61 publications
(83 reference statements)
2
24
0
Order By: Relevance
“…In our study, SF were found only in two indoor samples at average concentrations (0.02‐0.05 × 10 3 m −3 ) and were significantly below the spore concentrations. These data are consistent with previous findings in sawmills, but departs largely from levels measured in aerosolization studies and (1, 3)‐β‐glucans‐based projections, that is, that the spore concentrations are significantly higher than that of submicron fragments. The low levels of SF in present study may be due to the differences in the aerosolization mechanisms governing the release of these particles from fungal biomass in the indoor settings as compared to laboratory experiments.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study, SF were found only in two indoor samples at average concentrations (0.02‐0.05 × 10 3 m −3 ) and were significantly below the spore concentrations. These data are consistent with previous findings in sawmills, but departs largely from levels measured in aerosolization studies and (1, 3)‐β‐glucans‐based projections, that is, that the spore concentrations are significantly higher than that of submicron fragments. The low levels of SF in present study may be due to the differences in the aerosolization mechanisms governing the release of these particles from fungal biomass in the indoor settings as compared to laboratory experiments.…”
Section: Discussionsupporting
confidence: 88%
“…The procedure used here was described elsewhere . Briefly, the composition of fungal aerosols including spores (S), submicron fragments (SF, length: 0.2‐1 µm), and larger fragments (LF, length: >1 µm) in the samples was assessed using a FESEM (SU 6600 HITACHI) operated at low vacuum (25‐30 Pa) and in the back‐scattered electron (BSE) imaging mode.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Optical techniques include measuring the cumulative particle number concentration (particulate matter size distribution) based on size 46 rather than mass using an optical particle counter 47 since it has recently been found that large fungal fragments (>1µm) are under-sampled by traditional monitoring approaches, thereby underestimating actual fungal exposure. 48 Regardless of methodology, it is very important to collect suitable controls for the outdoor area as well as from the complaint/region of interest areas as well as those immediately adjacent to such areas. Suitable indoor controls which include non-complaint rooms or regions should be collected.…”
Section: How and What Do We Measure?mentioning
confidence: 99%